Evaluating customer eligibility for consumptive financing: A scoring system approach - Nurlita, Okky Budi; Marliyah, Marliyah; Bi Rahmani, Nur Ahmadi (LPMP Imperium, 2024)
This research investigates how Syariah Bank evaluates consumer financing customers using a scoring system to ensure appropriate assessments for financing approvals. By analyzing customer eligibility, the bank aims to minimize financing risks, enhance efficiency, and maintain stability, which can lead to increased consumer financing. The study uses descriptive qualitative methods to gather data through observation, interviews, and case studies at a Syariah Bank in Medan City. Findings emphasize the importance of assessing customer suitability for the effective functioning of the bank's financing system. The study identifies civil servant employees with salaries deposited in the bank as preferred candidates for consumptive financing. A well-implemented scoring system can reduce bad debt risks and boost customer confidence in financing transparency. Additionally, it encourages future studies to create more adaptive scoring models in response to evolving consumer behavior and economic conditions. Public interest statements This study's results are expected to significantly contribute to the banking sector, especially in improving the effectiveness of customer eligibility assessment through a scoring system. With proper implementation, this system can minimize the risk of bad debts and increase customer confidence in the transparency and accuracy of financing assessments. Article Info: Received 6/29/2024 | Revised: 9/16/2024 | Accepted: 9/19/2024 | Online First 9/27/2024